Intergenerational Relations in Educational Trajectories of Young (Children of) Migrants in Buenos Aires, Argentina - Alejandra González, Mariana (2022)
This article examines certain characteristics of the educational trajectories of young migrants at the secondary level in the Metropolitan Area of Buenos Aires (AMBA). It follows the aim to analyze the intergenerational relationships that are structured, in part, from such trajectories. In order to that, it has been designed a qualitative research, with different data collection techniques and with a sample composed by young people who belonged to foreign families, adults migrants, tutors and teachers from primary, secondary schools, and popular high schools. As a result of this research, three types of intergenerational relationships are proposed: the first one is focused on the way parents participated, which show variation between lax to more rigid forms; a second one, based on exchanged relations (gift-against gift), in which certain rights and duties are consolidated; and finally, another type of relation based on the transmission of a legacy, about the wish of achieve some upward mobility through education.